2018
DOI: 10.5858/arpa.2018-0124-oa
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Reflectance Confocal Microscopy for Diagnosis of Skin Lesions: An Update

Abstract: Context.— Histopathology is the current standard to diagnose skin disease. However, biopsy may not always be feasible, such as in patients with multiple nevi, a patient with a lesion on an aesthetically significant site, or in children. Recently, noninvasive techniques, including reflectance confocal microscopy (RCM), optical coherence tomography, and Raman spectroscopy, have enabled dermatologists to manage skin lesions in real time without the need for biopsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…RCM is a widely used tool that enables real‐time, visualization of skin layers on a horizontal plane, and serial optical sections of the lesions from the epidermis to the depth of 200‐300 µm 6 . Its high cellular resolution is close to that of conventional histology 7 . This feature is particularly useful in head and neck examinations, where it potentially avoids surgical operations in anatomically dangerous areas and areas that affect aesthetics.…”
Section: Introductionmentioning
confidence: 84%
“…RCM is a widely used tool that enables real‐time, visualization of skin layers on a horizontal plane, and serial optical sections of the lesions from the epidermis to the depth of 200‐300 µm 6 . Its high cellular resolution is close to that of conventional histology 7 . This feature is particularly useful in head and neck examinations, where it potentially avoids surgical operations in anatomically dangerous areas and areas that affect aesthetics.…”
Section: Introductionmentioning
confidence: 84%
“…4 Meanwhile, RCM is horizontal imaging, enabling a more clear and comprehensive observation of the interface layer. 4 Previous studies have shown that the characteristics of RCM images in interface dermatitis were highly consistent with the pathological changes under light microscopy 5 and RCM was able to detect intraepidermal and sub-epidermal blisters, respectively, in 50% and 75% of the patients affected by pemphigus and bullous pemphigoid. 6 Therefore, we tried to observe PNP lesions with RCM and achieved satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Sex and race concordance between physicians and patients is associated with improved perceptions of clinical care. 1 In 2017, 48.9% and 64.5% of dermatology attendings and residents, respectively, were female. 2 Academic dermatology leadership positions are underrepresented in sex and ethnic diversity.…”
mentioning
confidence: 99%
“…To the Editor: Reflectance confocal microscopy (RCM) is a noninvasive imaging technique used to assess skin lesions. 1 Although it has been shown to identify skin cancer with high levels of diagnostic accuracy, 1,2 little is known about its impact on health care costs.…”
mentioning
confidence: 99%